(untitled) (Journal of Hama University, 2024)
The research aimed to measure and analyze the behavior of each of the cost of goods sold, total marketing, administrative and general costs, and operational costs in the Abu Dhabi Securities Exchange. The statistical population of the research was represented by the industrial companies listed on the Abu Dhabi Securities Market, which numbered (21) industrial companies, and due to the lack of data available for the entire statistical community during the period from 2014 to 2021, the current research was limited to (9) industrial companies. The secondary data related to the research variables were obtained from the income statement of the companies using the model of Anderson et al. (2003), and analyzed it based on the method of ordinary least squares (OLS) through the SPSS.V.25 statistical package program. The results of the research showed that each of the cost of goods sold and operating costs behaved asymmetrically and Sticky, Where costs increased by (62.8%) and (63.9%), respectively, when sales revenue increased by 1%, while they decreased by (35%), ( 38.6%, respectively, when sales revenue decreased by 1%, The research also found that the Stickiness of each of the cost of goods sold and operating costs increased at a low level of debt intensity and a high level of company size, while no effect was found for asset intensity and free cash flow rate on the behavior of each of the cost of goods sold and operating costs.